1992
DOI: 10.1113/jphysiol.1992.sp019259
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ current and charge movement in adult single human skeletal muscle fibres.

Abstract: SUMMARY1. The Vaseline-gap technique was used to record calcium currents (ICa) and charge movement in single cut fibres from normal human muscle. Experiments were carried out in 2 or 10 mM-extracellular Ca2" concentration ([Ca2+].) and at 17 or 27 'C.2. The passive electrical properties of the fibres with this technique were: membrane resistance for unit length rm = 59-4 kQ cm; longitudinal resistance per unit length ri = 4-9 MQ/cm; longitudinal resistance per unit length under the Vaseline seals re = 438 MC/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
25
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
7
25
2
Order By: Relevance
“…In human muscle, as in rat muscle, the best fit was obtained with a one exponential function in the whole range of membrane potentials. In human muscle fibre, peak ICa is smaller than in rat fibres and the ICa activation time constant is slower than in rat fibres (Garcia, McKinley, Appel & Stefani, 1990). The reported differences in the activation kinetics between mammalian and frog skeletal muscle fibres could be related to different characteristics of the Ca2+ channel activation in mammalian fibres and/or to inadequacy of the voltage clamp of tubular membranes in frog skeletal muscle fibres that would give rise to a radial delay in Ca2+ channel openings.…”
Section: Action Of Als Igg On Charge Movementmentioning
confidence: 84%
See 1 more Smart Citation
“…In human muscle, as in rat muscle, the best fit was obtained with a one exponential function in the whole range of membrane potentials. In human muscle fibre, peak ICa is smaller than in rat fibres and the ICa activation time constant is slower than in rat fibres (Garcia, McKinley, Appel & Stefani, 1990). The reported differences in the activation kinetics between mammalian and frog skeletal muscle fibres could be related to different characteristics of the Ca2+ channel activation in mammalian fibres and/or to inadequacy of the voltage clamp of tubular membranes in frog skeletal muscle fibres that would give rise to a radial delay in Ca2+ channel openings.…”
Section: Action Of Als Igg On Charge Movementmentioning
confidence: 84%
“…However, human fibres develop smaller and slower ICa than rat cells at the same temperature. The limiting PCa was 1-24 x 10-5 cm s-1 and 1-48 x 10-6 cm s-I in rat and human fibres, respectively; the time constant of activation was 44-8 + 1-4 ms (0 mV, 2 mMCa2+) and 90 5 + 6-0 ms (30 mV, 10 mM-Ca2+) in rat and human skeletal muscle, respectively (Garcia et al 1990). …”
Section: Action Of Als Igg On Charge Movementmentioning
confidence: 99%
“…Since one of the functions of calcium channel molecules is to transfer calcium ions into the cells, this process could be one of the potential candidates for contributing to the calcium entry and accumulation in DMD cells. In vitro studies on aneurally cultured cells have shown the existence of at least two types of voltage-dependent calcium current (T and L); their characteristics have been extensively studied in normal (Rivet et al 1990(Rivet et al , 1992Garcia et al 1992;Sipos et al 1997;Morill et al 1998;Harasztosi et al 1999) and DMD muscle cells (Rivet et al 1990), but no obvious differences in the voltage dependence and kinetics of these calcium currents have been observed, as expected from cells in which the resting intracellular calcium concentration remained similar. Consequently, in order to address a possible involvement of such calcium channels in the detected intracellular calcium concentration elevation, investigations in co-cultured human muscle cells were essential despite the low availability of DMD biopsies.…”
mentioning
confidence: 99%
“…In addition they permit an extremely slow calcium inward current (L_type current) whose physiological role is still unclear (for a review see Melzer et al 1995). L_type current characteristics have been extensively studied in adult amphibian and mammalian skeletal muscle (for references see Delbono, 1992;Feldmeyer et al 1990Feldmeyer et al , 1992Feldmeyer et al , 1995Garcia et al 1992;Francini et al 1996). On the other hand, important data on structure-function relationships of the channel have been obtained by heterologous expression of recombinant DHP receptors in cultured immature muscle cells (myotubes) (Tanabe et al 1988;Garcia et al 1994).…”
mentioning
confidence: 99%
“…The characteristics of this type of inactivation have not yet been fully determined in any skeletal muscle preparation and particularly little information is available from human preparations which have recently attracted attention due to the discovery of L_type Ca¥ channelrelated diseases (Jurkat-Rott et al 1994;Ptacek et al 1994;Monnier et al 1997). A few studies describe voltagedependent activation and inactivation in human muscle cells (Rivet et al 1990(Rivet et al , 1992Garcia et al 1992;Sipos et al 1995;Lehmann-Horn et al 1995;Jurkat-Rott et al 1998) but no data are available on the dynamics of the transition to and the recovery from the inactive state(s). The purpose of the present investigation was to characterize these processes in cultured myocytes.…”
mentioning
confidence: 99%